CONCEPTUAL DIMENSION OF SYSTEMATIC APPROACH TO THE ORGANIZATION MANAGEMENT - Maltsev, Eduard (Proceedings of National Aviation University (archive), 2016)
Purpose: The systematic representation of the individual and the organization at the conceptual level is a powerful tool to understand and design an organization as a whole. The systematic approach called to deal to the complexity of modern organizations while the use of abstraction let properly represent the relationships in the system. There are not too many attempts to combine the conceptual representation of organization and a person in the organization. Methods: We formulate a cross-cutting logic of creating links between personal and organizational concepts in the systematic approach to strategic management. It is shown that such representation is possible in the same conceptual frame: description, values, goals, mechanisms. The logic let ensure the clearness in providing integrity of the organization at the conceptual level and therefore influence people's behaviour at work in a direction desired for the whole system. Results: It is shown that the use of a conceptual frame allows to describe an organization through the substrate (Self-concepts of employees), concept (creating value for stakeholders) and relationships (embeddedness of the concept into the substrate –Self-concepts of employees). Suggested cross-cutting logic let establish the links between personal and organizational concepts. The core in the logic is correct representation of the organization and a person at conceptual level. Discussion: The definition of the Self-concept of each employee in the same conceptual frame is not trivial task due to the difficulty of adequate "measuring of oneself", abstraction and self-description in a given frame. Very common, for example, is the discrepancy between perceptions of itself and perception about the person of others. The development of methods of forming linked and holistic conceptual representations of personality and organization is an important topic for future research.